Zdejmowanie klątwy, odczynianie uroku. Narracja głosowa we współczesnym serialu - Żyto, Kamila (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2026)
In the late 1980s, Sarah Kozloff’s Invisible Storyteller: Voice-over Narration in American Fiction Film (1988) emerged as foundational work in the field of film studies. To date, the book remains virtually the sole monograph dedicated to the study of voice-over narration in film. Subsequently, there has been a paucity of scholarly articles examining this subject, particularly from a theoretical perspective. As a result, the inquiries presented by the British researcher over thirty years ago merit a revisit. The article seeks to investigate the evolution and application of voice-over in premium series available on streaming platforms. Its objective is to demonstrate that this narrative device has experienced a remarkable resurgence. In the era of so-called ‘complex TV,’ voice-over is increasingly employed in diverse and unconventional manners. As with other storytelling elements, it proves instrumental in fostering ambiguous interactions between the character and the depicted world. Furthermore, it possesses significant potential to influence the dramaturgical dynamics of a narrative, as evidenced by the examples of quality series such as Mr. Robot, Fleabag, or 13 Reasons Why.